PENGARUH PEMAHAMAN, PENERAPAN E-SYSTEM, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Nabila Khairunnisaa (2022)
This study aims to determine how much influence understanding of tax regulations, application of e-system, and awareness of taxpayers have on individual taxpayer compliance. This study uses a quantitative method, sample used in this study is an individual taxpayer registered in East Jakarta. The sampling technique used in this study is Convenience Sampling with the respondents' criteria used in this study is individual taxpayers who are registered at KPP Jakarta and have an NPWP. Convenience sampling is a collection of information obtained from members of the population with their consent to provide that information. The sample used in this study is 100 individual taxpayers registered in East Jakarta. This hypothesis testing uses Structural Equation Modeling (SEM) with Lisrel 8.8 tool. The test results show that (1) there is a significant positive effect between understanding tax regulations on taxpayer compliance, (2) there is a significant positive effect between the implementation of the e-system on taxpayer compliance, and (3) there is no effect between taxpayer awareness on taxpayer compliance.